Aalto-1, multi-payload CubeSat: In-orbit results and lessons learned. (October 2021) - Mughal, M. Rizwan; Praks, J.; Vainio, R.; Janhunen, P.; Envall, J.; Näsilä, A.; Oleynik, P.; Niemelä, P.; Nyman, S.; Slavinskis, A.; Gieseler, J.; Jovanovic, N.; et al.
Abstract: The in-orbit results and lessons learned of the first Finnish satellite Aalto-1 are briefly presented in this paper. Aalto-1, a three-unit CubeSat which was launched in June 2017, performed Aalto Spectral Imager (AaSI), Radiation Monitor (RADMON) and Electrostatic Plasma Brake (EPB) missions. The satellite partly fulfilled its mission objectives and allowed to either perform or attempt the experiments. Although attitude control was partially functional, AaSI and RADMON were able to acquire valuable measurements. EPB was successfully commissioned but the tether deployment was not successful. In this paper, we present the intended mission, in-orbit experience in operating and troubleshooting the satellite, an overview of experiment results, as well as lessons learned that will be used in future missions. Highlights: The launch and operations of first Finnish satellite, Aalto 1. In orbit results and lessons learned of first miniaturized hyperspectral imager onboard a CubeSat. In orbit results and lessons learned of miniaturized low power radiation monitor. In orbit results and lessons learned of electrostatic plasma brake. In orbit results and lessons learned of CubeSat platform.